Gangguan Fungsi Kognitif pada Penderita Diabetes Melitus (DM) Tipe 2 - Sumaiya Junarsih Silehu; Nur Wahyuni Munir; Wa Ode Sri Asnaniar (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Diabetes Mellitus (DM) is one of the ten health problems according to the World Health Organization (WHO) that causes death and disability globally. Diabetes is also associated with an increased chance of cognitive decline as determined by the MMSE score. Chronic exposure to hyperglycemia can reward cognitive function because apart from causing schizophrenia, this disease can also lead to other cognitive dysfunction diseases such as Alzheimer's and dementia. This study aims to describe cognitive dysfunction in patients with type 2 Diabetes Mellitus at Faisal Islamic Hospital Makassar. The research design used in this research is qualitative research with a naturalistic approach. The number of samples carried out with non-probability sampling technique with a large sample of 67 people. Relationship test was carried out using the Chi-Square statistical test with a significance level of α <0.05. The results showed that there was a significant relationship between high blood sugar and impaired cognitive function in type 2 DM patients (p=0.00 <0.05). The conclusion of this study is that there is a relationship between increased blood sugar and cognitive dysfunction problems in type 2 Diabetes Mellitus (DM) patients at Faisal Islamic Hospital, Makassar City.